The Neuronal Representation of Pitch in Primate Auditory Cortex - Bendor, Daniel (2005)
Pitch perception plays a critical role in identifying and segregating auditory objects1, especially in the context of music and speech. The perception of pitch is not unique to humans and has been experimentally demonstrated in several animal species2,3. Pitch is the subjective attribute of a sound’s fundamental frequency (f(0)), that is determined by both the temporal regularity and average repetition rate of its acoustic waveform. Spectrally dissimilar sounds can have the same pitch if they share a common f(0). Even when the acoustic energy at f(0) is removed (“missing fundamental”) the same pitch is still perceived1. Despite its importance for hearing, how pitch is represented in the cerebral cortex remains unknown. Here we show the existence of neurons in the auditory cortex of marmoset monkeys that respond to both pure tones and missing fundamental harmonic complex sounds (MFs) with the same f(0), providing a neural correlate for pitch constancy1. These pitch-selective neurons are located in a restricted low-frequency cortical region near the anterolateral border of primary auditory cortex (AI), consistent with the location of a pitch-selective area identified in recent human imaging studies4,5.